Development of Learning Package for Enhancing Reading and Writing Achievement in Thai for Communication Course for Undergraduate Students - Sasipong Srisawat (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
The objectives of this study were 1) to develop learning packages to improve reading and writing performance in Thai for undergraduate students' communication course to meet the 80/80 criteria, 2) to compare the learning outcomes of the learning packages using pre- and post-tests, and 3) to investigate students' attitudes toward the learning packages. The research instrument used in the current study was the learning package. The sample group included 50 students enrolled in the Thai for Communication course. The statistics used in the data analysis were percentage, mean, standard deviation, and t-test. The results of the investigation were as follows: 1) the learning package was used to promote reading and writing performance in Thai language communication course, the quality was of high and efficiency according to the standard criteria, 2) the Thai language reading and writing performance, after learning with the learning package, was significantly higher than before learning at the .05 level, and 3) the students' attitude toward learning with the learning package was at the extremely high level.